A longitudinal examination of a psychoeducational intervention and a respite grant for family caregivers of persons with Alzheimer's or other dementias - Smith, Sara Anne, author; Bell, Paul A., advisor; Nelson, Tracy, committee member; Borrayo, Evelinn, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2006)
Alzheimer's disease can be particularly devastating to those who are caring for their loved one with the condition. Interventions such as support groups, caregiver training, and respite services can be effective in improving quality of life for those with dementia and their family caregivers, but there are few longitudinal studies that last more than 6 months to a year that have examined the longer-term implications of such interventions. The Colorado Alzheimer's Disease Demonstration Grants to States Project initiated in 2002 provided a valuable opportunity to compare psychoeducational, respite grant, and the combination of these two interventions in rural and urban communities across an 18-month period. A total of 82 caregivers participated in the study with 22 in the Savvy Caregiver Program (Savvy), 41 receiving a voucher-type respite grant for up to $1,000, and 19 receiving both. Participants completed multiple surveys and questionnaires both before the training and at 6 -, 12-, and 18-month follow-up phone interviews. Positive outcomes of the training, grant, and multicomponent intervention were found at the follow-ups in spite of natural declines in the loved one's ability to perform Activities of Daily Living (ADL's) and increases in problem behaviors. Specifically, no group increases in depression were found at 18-month follow-up, although there was individual variation and the grant intervention appeared to be best at maintaining the improvement in depression initially observed at 6 months. In addition, the Savvy intervention showed significant decreases in depression across the 18 months. Varieties of service usage increased especially in the combination group and for urban participants receiving a grant since these participants were given funds to purchase services. There were no changes in service usage from 12 months to 18 months. All three interventions seemed to get about 30 percent of participants to start attending support groups, and there were no substantial differences in attendance attributable to the interventions at 18-month follow-up. The fact that caregiver depression did not increase on average over time even though problem behavior did, further implies a benefit of the interventions.
Keywords: social psychology; psychotherapy; intervention; families and family life; caregivers; Alzheimer's disease; dementia; clinical psychology